Health Care Functions of Elderly Families with Hypertension Who Live Alone Life in Bandung District (Phenomenological Study) - Budiman, Budiman; Dedi, Blacius; Mendrofa, Fery Agusman Motuho; Hastuti, Witri; Hani, Umi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: The aim of this research is to explore the health care function of families of elderly people with hypertension who live their lives alone in Bandung Regency. Methods : This research design uses a qualitative method with an exploratory phenomenological approach. The number of participants was 7 people who conducted a focus group discussion (FGD). Results : The results of this research obtained 5 themes, namely recognizing internal and external health problems based on reflex response, making decisions based on personal needs and complaints of the elderly, caring for oneself by preventing and strengthening positive energy, maintaining environmental health through dividing tasks and joint financial responsibility, and increasing optimization utilization of health services. Conclusions : Research on elderly hypertension families reveals five main themes: understanding hypertension through psychological and physical responses, making decisions based on personal needs, self-prevention and positive energy, dividing environmental health and joint financial responsibility, and optimizing health facility use through PKM and Health Services.